Five Dynasties and Ten Kingdoms - Lorge, Peter Allan, 1967- (Book collections on Project MUSE.)
"The period of the Five Dynasties and Ten Kingdoms (907-960) has long been treated as an anomaly in the history of China, an age of great disunity between the empires of the Tang and the Song dynasties. Breaking with previous scholarship on China's middle period, this edited volume presents individual studies that focus on the art, culture, and politics of the interregnum, challenging underlying assumptions about the unitary nature of dynastic culture and its value as a category of historical analysis. It understands these decades as a time of important transition in which the incipient cultural shifts of the mature Tang dynasty turned into the foundations of Song society. Consequently it highlights the complex narrative processes that gave birth to Song culture."--Publisher's web site.